Prone Positioning terhadap Status Oksigenasi pada Pasien COVID-19 - Rohmat Rohwandi; Hotma Rumahorbo; Susilawati Susilawati; Linlin Lindayani; Asep Badru Djamaludin (Jurnal Keperawatan Silampari, 2022)
This study systematically reviews the effectiveness of Prone Positioning on the oxygenation status of COVID-19 patients from the existing literature. The research method uses a systematic literature review and meta-analysis obtained from the google scholar database. Proquest, Pubmed, Science Direct, and Semantic Scholar. The results showed that based on oxygenation parameters, Prone Positioning had an effect on changes in the ROX index value (Mean Difference 3.89, 95% CI 0.08 to 7.70, P = 0.05), P/F Ratio (Mean Difference 17.88, 95% CI 5.44 to 30.33 , P=0.05), SPO2 (Mean Difference 1.98, 95% CI 1.29 to 2.68, P<0.00001), and S/F Ratio (Mean Difference 23.04, 95% CI 15.89 to 30.19, P <0.00001), while the respiratory rate parameters (Mean Difference -0.79, 95% CI -1.76 to -0.18, P=0.11) and PaO2 (Mean Difference 7.75, 95% CI -22.80 to -38.31, P= 0.62) did not show a significant difference. In conclusion, Prone Positioning is considered to significantly affect changes in the oxygenation of COVID-19 patients. It is expected to be a reference in implementing nursing interventions for oxygenation disorders in patients. Keywords: COVID-19, Oxygenation, Positioning, Prone